The Effect of Aluminum Wire Winding Patterns on Partial Discharge Occurrence in 24 kV Insulator Strings - Tanthanuch, Nutthaphong; Srisomchai, Sirirod; Uchaipichat, Nopadol (Engineering, Technology & Applied Science Research, 2025)
This study investigates Partial Discharge (PD) on aluminum wire insulators for 24 kV transmission lines. Using the IEC 60270 charge measurement, PD was evaluated on line post 57-2, line post 57-3, and pin post 56/57-2 insulators. A metallic pipe modeled the transmission line, with aluminum wire wound in straight and curved patterns as per Thailand's PEA standards. A test voltage of 10–25 kV was applied, and the Phase Resolved Partial Discharge (PRPD) analysis identified corona discharge as the primary PD type. The results showed increased PD magnitude and frequency at higher voltages, peaking at 90° and 270° phase angles. In addition, the pin post insulator and straight winding produced the highest PD. This study highlights the impact of wire winding patterns on PD, an often-overlooked factor. The simple, cost-effective evaluation method provides insights for optimizing insulation, maintenance, and real-time monitoring in high-voltage systems, benefiting applications such as cable spacers and lightning arresters.